Vertical Hydroponic Monitoring System Using Internet of Things - Ibrahim, Dhiya Akmal; Muhammad Audah, Lukman Hanif (Evolution in Electrical and Electronic Engineering, 2023)
Hydroponic systems have gained popularity in recent years due to their ability to cultivate plants without the use of soil, resulting in increased efficiency and reduced resource consumption. Maintaining ideal growth conditions in hydroponic systems, on the other hand requires constant monitoring of essential variables like as pH, TDS (Total Dissolved Solids), water level, and temperature. This paper describes a vertical hydroponic monitoring system that utilises a pH sensor, TDS sensor, ultrasonic sensor, and DS18B20. The system includes an ESP32 microcontroller, which serves as the central processing unit, collecting data from sensors and wirelessly transmitting it to a Blynk platform. The pH sensor determines the acidity or alkalinity of the nutrient solution. The TDS sensor detects the concentration of dissolved minerals in the water. The ultrasonic sensor precisely measures the water level in the hydroponic reservoir. The DS18B20 sensor used to monitors water temperature. The results obtained from this study are from Blynk graph, providing comprehensive insights into environmental conditions in terms of pH level, TDS level, water temperature and water level. The work used DFT type hydroponics method to grow water spinach. The estimated time required to obtain mature plant growth and to collect all the necessary data for analysis is one month.